A Study on Training Factors and its Impact on Training Effectiveness in Kedah State Development Corporation, Kedah, Malaysia - Hu, Yanan (2011)
The main objective of this study is to measure the impact of training on human resource practices as well as to identify the factors those are related to effectiveness of training. The variables examined were demographics characteristics (age, gender, martial status, education level and length of working in current job), types of training, training environment and work environment . A total of 92 questionnaires were distributed to the respondents in Kedah State Development Corporation (KSDC) company. This study was designed to identify through questionnaire survey, the factors that can contribute towards training effectiveness. The results of the study found that training environment and work environment significantly affect raining effectiveness .The study provides baseline data from which the training effectiveness can be assessed and improved upon so that higher benefits can be obtained by the organization.